The Trade-Off between Foreign Direct Investments and Exports: The Role of Multiple Dimensions of Distance - Maureen Lankhuizen; Henri L.F. de Groot; Gert-Jan M. Linders (Tinbergen Institute, 2009)
To serve foreign markets, firms can either export or set up a local subsidiary through horizontal Foreign Direct Investment (FDI). The conventional proximity-concentration theory suggests that FDI substitutes for trade if distance between countries is large, while exports become more important if scale economies in production are large. This paper investigates empirically the effect of different dimensions of distance on the choice between exports and FDI. We find that different dimensions of distance affect exports and FDI differently. There is clear evidence of a proximity-concentration trade-off in geographical terms: the share of FDI sales in total foreign sales (exports and FDI sales) increases with geographical distance. The positive relation between import tariffs and FDI intensity provides further evidence for a trade-off resulting from trade costs. On the other hand, the share of FDI decreases with language differences and cultural and institutional barriers. The latter dimensions of distance thus affect FDI more strongly than exports.
Keywords: F14; F21; F23; 330; cultural distance; institutions; FDI and trade; spatial interaction models; Auslandsinvestition; Multinationales Unternehmen; Export; Geographische Entfernung; Handelseffekt; Gravitationsmodell; Theorie; Schätzung; Welt